Optimization of autohydrolysis of olive pomaces to obtain bioactive oligosaccharides: The effect of cultivar and fruit ripening - Freitas, Laura (2022)
The valorisation of agro-industrial residues presents a challenge in obtaining economically sustainable and environmentally friendly industrial processes. Olive pomace is a by-product generated in large quantities, from olive oil extraction. This residue mostly consists of lignocellulosic materials. The aim of this study was to evaluate the potential use of extracted olive pomaces (EOP) obtained from olives with different ripening indexes (RI) and from different cultivars (Cobrançosa; RI = 2.5; 3.3 and 4.7; and Galega Vulgar; RI = 1.8; 2.9 and 4.8), to produce bioactive oligosaccharides from hemicelluloses by autohydrolysis. The hydrothermal treatment conditions were optimized by Response Surface Methodology, following a central composite rotatable design (CCRD), as a function of temperature (T: 142–198 °C) and time (t: 48–132 min), corresponding to severity factor (SF) values from 3.2 to 4.9. For all pomace samples, soluble sugar production was described by concave surfaces as a function of temperature and time. Autohydrolysis with SF equal or higher than 4.0 produced higher sugar yields, with maximum values around 180 g glucose equivalent/kg EOP for SF of 4.7 (190 °C/120 min) or 4.9 (198 °C/90 min). These values were similar for both cultivars and were not dependent on the ripening stage of the olives. Maximum oligosaccharide (OS) yields of 98% were obtained by autohydrolysis with SF of 4.0. The increase in SF to 4.9 resulted in a decrease in OS yield to 86–92%, due to the release of monomeric sugars. The monosaccharides were mostly xylose (55.8–67.7% in Galega; 50.4–69.0% in Cobrançosa liquid phases), and glucose, galactose, arabinose and rhamnose, in smaller quantities. Therefore, the production of bioactive xylo-oligosaccharides (XOS) from olive pomaces mainly depends on the hydrothermal conditions used.